A description of the bite mark identification ability of alginate impression on students at Dental Faculty of Prof. Dr. Moestopo University - Pricillia P. Sianita (Journal of Dentomaxillofacial Science, 2018)
Objective: Trying to explain the extent to which our students’ ability to identify, through dentition, a bite mark injury.Material and Methods: As many as 30 students in the Dental Faculty of Prof. Dr. Moestopo University involved in this study demonstrated their ability to identify traces left behind from the experimental bite mark of alginate impression. The data obtained will be tabulated to explain the subject's ability to identify the bite mark injury.Results: The data showed that the identification ability of subject of senior-semester students is lower than that of junior-semester students. The identification ability of the student decreases with the time elapsed since when the related lesson (dental anatomy) is given. Dental anatomy was given in the first semester and the lowest score of identification ability indeed achieved by subjects in the highest semester (senior students at semester eight involved in this program study).Conclusion: In this case, it is evident that repetition is an important factor in a learning process, and therefore, it is necessary to think of a way to do it appropriately in the curriculum of the dentist education program in our faculty.